Organizing Educational Processes On The Basis Of Information Technology - DILSHOD YULDASHEV; GULBAKHOR SOLIYEVA (Universitas Muhammadiyah Sidoarjo, 2022)
Our Republic is also moving towards an informed society due to independence. This issue is one ofthe first issues in the focus of our President and government. Today, the Internet has emerged as a fast andreliable source of information. The development of the information world has undergone dramatic changes andnew information technologies have emerged. There has been a lot of talk lately about the Internet, itscapabilities, and e-mail. The terms